The Influence of Jogjakarta Outer Ring Road Development Plan on the National Roads in the Special Region of Yogyakarta - Prima J. Romadhona; Affan Gaffarudin; Thareq I. Tanza; Arief R. Wiwaha (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2021)
The Influence of Jogjakarta Outer Ring Road Development Plan on the National Roads in the Special Region of Yogyakarta